2015
DOI: 10.1160/th14-12-1027
|View full text |Cite
|
Sign up to set email alerts
|

The cost-utility of dabigatran etexilate compared with warfarin in treatment and extended anticoagulation of acute VTE in the UK

Abstract: The relative efficacy and safety of dabigatran etexilate and warfarin have been evaluated in two head-to-head, phase III, treatment of acute venous thromboembolism (VTE) trials, and one extended prophylaxis trial, in patients with high risk of recurrent VTE. Dabigatran etexilate demonstrated similar efficacy to warfarin, and was associated with a reduced risk of major or clinically relevant bleeds. Based on results of these trials, and real-life disease prognosis following discontinuation of anticoagulation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…While apixaban, edoxaban, and rivaroxaban have a better safety profile over VKA for the acute management [3942], DOAC were only associated with trends for reduced MB and their net clinical benefit were similar during extended anticoagulation compared to VKA. Pharmacoeconomic studies also suggested that apixaban, dabigatran and rivaroxaban were cost-effective alternatives to VKA for extended anticoagulation following acute VTE in Canada, United Kingdom, and United States of America [4751], although these studies were funded by pharmaceutical companies. Ultimately, the choice of treatment for extended anticoagulation thus likely relies on patients’ preference and individual risk factors for adverse events with VKA and DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…While apixaban, edoxaban, and rivaroxaban have a better safety profile over VKA for the acute management [3942], DOAC were only associated with trends for reduced MB and their net clinical benefit were similar during extended anticoagulation compared to VKA. Pharmacoeconomic studies also suggested that apixaban, dabigatran and rivaroxaban were cost-effective alternatives to VKA for extended anticoagulation following acute VTE in Canada, United Kingdom, and United States of America [4751], although these studies were funded by pharmaceutical companies. Ultimately, the choice of treatment for extended anticoagulation thus likely relies on patients’ preference and individual risk factors for adverse events with VKA and DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…All of them suggested that DOACs are costeffective relative to VKA. 100,[104][105][106][107][108][109][110][111][112][113][114][115][116] Finally, we considered DOACs to be acceptable and feasible to implement in most scenarios. However, given their cost, some patients might not be able to afford them.…”
Section: Other Etd Criteria and Considerationsmentioning
confidence: 99%
“…The company assumed that all bleeds were major, stating that no studies were identified that reported the proportion of bleeds classified as major or minor following an elective invasive procedure in this population, and that minor bleeds would be expected to have a minor impact on costs and QALYs. Therefore, a disutility associated with a major bleeding event of 0.397 for a duration of 1 week was adopted from Jugrin et al 84 For thrombus-related AEs, the company incorporated a disutility of 0.029, applied over 1 week, estimated by Jugrin et al 84 for related thrombotic events (index deep-vein thrombosis and index pulmonary embolism).…”
Section: Utilities Summarymentioning
confidence: 99%
“…Disutilities for bleeding events and thrombotic events were also identified from the literature by Shionogi. Disutilities of 0.397 for major bleeding events and of 0.122 for clinically relevant non-major bleeding events were identified from Jugrin et al 84 The AG base-case model included only bleeding AEs of ≥ grade 3, which were assumed to be equivalent to major bleeding events. Therefore, the disutility of 0.397 for major bleeds was incorporated into the model base case, with a duration of 1 week.…”
Section: Utilitiesmentioning
confidence: 99%